A potentially protective role of IL-18 Binding Protein in HIV-infected Long-Term Non-Progressors. (February 2017) - Iannello, Alexandre; Samarani, Suzanne; Allam, Ossama; Jenabian, Mohammad-Ali; Mehraj, Vikram; Amre, Devendra; Routy, Jean-Pierre; Tremblay, Cécile; Ahmad, Ali
Highlights: IL-18BP, an antagonist of IL-18, production decreases in HIV infected individuals. No increase in production of IFN-γ in HIV infection may underlie this decrease. Its production is maintained at normal physiological levels in LTNP. The antagonist levels correlate negatively with viral loads. The levels tend to correlate positively with CD4+ T cell counts. Abstract: An imbalance between IL-18 and its antagonist, IL-18 Binding Protein, occurs in the circulation of HIV-infected individuals. We show here for the first time that HIV-infected Long Term Non-Progressors (LTNPs) do not develop this imbalance, and maintain normal levels of IL-18BP in the circulation. Their circulating levels of the antagonist correlate negatively with viral loads and show a positive trend with CD4+ T cells counts. The maintenance of normal production of IL-18BP may contribute, at least in part, to the ability of LTNPs to delay AIDS progression.